APPLYING SERVQUAL, TAM AND IMPORTANCE PERFORMACE ANALYSIS TO EXPLORE USER EXPERIENCE OF SAYURBOX - Purwandani, Indah; Syamsiah, Nufia Oktaviani; Rosmia, Mia; Nurwahyuni, Siti (Journal of Innovation And Future Technology (IFTECH), 2024)
The high disparity in prices of agricultural products between farmers and consumers raises special concerns. The prices paid by consumers are high, while farmers as producers receive low prices. The many distribution chains that must be passed from farmers to consumers are the main cause of this disparity or difference. The phenomenon related to increasing use of Sayurbox is still not accompanied by very good customer satisfaction. Many customers feel disappointed with the quality of the products and services provided by Sayurbox. This research aims to determine the level of service quality of the SayurBox application with the variables contained in Servqual, TAM and IPA. This research variable uses user perceptions and user expectations from five Servqual dimensions, namely Tangibles, Reliability, Responsiveness, Assurance, Empathy and 2 dimensions of the Technology Acceptance Model, namely Perceived Usefulness, Perceived Ease of Use. Data collection was carried out using an online questionnaire containing 24 questions representing the dimensions used. Next, the collected data will be analyzed using the four quadrants of the IPA method to find out management information and service quality strategies. Quadrant 1 Keep Up The Good Work has 9 indicators, Quadrant 2 Possible Overkill has 3 indicators, Quadrant 3 Low Priority has 6 indicators and Quadrant 4 Concentrate Over Here there are 6 indicators. It can be concluded that integrating the Service Quality (Servqual), Technology Acceptance Model (TAM) and Importance Performance Analysis (IPA) methods can provide analysis results related to the user experience of Sayurbox users.